The illustrated digital imaging dictionary - Grota, Daniel 1944-; Grotta, Sally Wiener 1949- (McGraw-Hill, 1998)
This practical guide to digital imaging defines terms likely to be encountered in product documentation. It aims to demystify digital imaging technology, and includes an overview of the field. It is suitable for both novice and more advanced users.